Patterns of Filipino migration to Guam United States military colonialism and its aftermath - Pobutsky, Ann M.; Neri, Enrico I. (Philippine studies : historical and ethnographic viewpoints, 2018)
"In the context of US military colonialism, this research note examines patterns of migrant Filipino employment in Guam using US census data. While Chamorros were in the majority in various occupational categoreis in 1920, by 1950 Filipinos dominated many categories, except in professional, technical, and managerial positions in which whites had preponderance. The surge of Filipino male migration to Guam owed to the need for skilled labor in postwar reconstruction. From 1970 onwards, Filipino migration to Guam increased, but so did other Asians, resulting in a labor situation in which no ethnic group was dominant in any one occupational category."